1996
DOI: 10.1097/00006842-199609000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Stress, Traits, Mood States, and Stressful Daily Events on Salivary Cortisol

Abstract: This study examined the effects of perceived stress and related individual characteristics, mood states, and stressful daily events on salivary cortisol levels. Forty-one "high stress" and 46 "low stress" subjects were selected on the basis of Perceived Stress Scale scores from a sample of male, white collar workers. Subjects completed Experience Sampling self-reports and collected saliva samples 10 times a day over 5 consecutive days. Multilevel analysis revealed that trait anxiety and depression, but not per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
297
9
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(333 citation statements)
references
References 59 publications
24
297
9
3
Order By: Relevance
“…This gives us reasonable cause to reject elevated stress levels as an effect mechanism. Perceived stress and actual stress are not perfectly correlated (21), however, and our study data do not give any insight into how physiological reactions to stress, such as cortisol or dehydroepiandrosterone sulfate (DHEAS) hormone changes, might mediate changes in BGLs. This is a relevant hypothesis that merits further investigation.…”
Section: Discussioncontrasting
confidence: 76%
“…This gives us reasonable cause to reject elevated stress levels as an effect mechanism. Perceived stress and actual stress are not perfectly correlated (21), however, and our study data do not give any insight into how physiological reactions to stress, such as cortisol or dehydroepiandrosterone sulfate (DHEAS) hormone changes, might mediate changes in BGLs. This is a relevant hypothesis that merits further investigation.…”
Section: Discussioncontrasting
confidence: 76%
“…To identify subjects reporting high vs. low perceived stress and maximize the number of subjects included in the analyses, a median-split approach on PSS scores was used. This approach is in line with prior studies that have used the PSS scale categorically to identify low vs. high PSS scorers (e.g., Kuiper, Olinger, & Lyons, 1986;Maes, Van Bockstaele, & Van Gastel, 1999;van Eck, Berkhof, Nicolson, & Sulon, 1996).…”
Section: Study 1 Methodssupporting
confidence: 72%
“…However, three studies found no associations between state PA and cortisol response (Ryff, Singer, . & Dienberg Love, 2004;Szczepanski et al, 1997;van Eck, Berkhof, Nicolson, & Sulon, 1996). Of the studies looking at endocrine parameters other than cortisol, several naturalistic studies examined epi and norepi, other "stress" hormones that act to increase blood flow and cardiovascular activity.…”
Section: Physiological Systems Associated With Healthmentioning
confidence: 99%